Adopting hyperledger fabric blockchain for EPCglobal network - CHUA, Pamela Hui Ting (Institutional Knowledge at Singapore Management University, 2019)
The EPCglobal Network is a computer network used to share product data between trading partners. The EPC Information Services (EPCIS) is an event record repository that allows disparate applications to access and query for data both within and across enterprises. Ultimately, this data sharing is aimed at enabling participants in the EPCglobal Network to gain a shared view of the disposition of EPC-bearing objects within a relevant business context [1].Despite the potential benefits, enterprises are reluctant to integrate into the EPCglobal Network due to the financial and manpower resources required to set up, operate and maintain the EPCIS and to adopt the standards. Issues like security, computation and storage overheads would also have to be managed. To solve the problem, this paper advocates a blockchain solution using Hyperledger Fabric to serve as a shared EPCIS across trading partners. The blockchain can be queried directly to facilitate information sharing subjected to access control rules. It also adheres to the EPCglobal Network standards. This approach provides several important benefits including eliminating the need for enterprises to maintain their own EPCIS while still being able to participate and benefit from the network. As the blockchain can be queried directly, the provision of EPC Discovery Services (EPCDS) may also be unnecessary. To explore this idea, we constructed a prototype using Hyperledger Composer and Hyperledger Fabric while adhering to the data elements, structures and formats as stated in the standards to ensure interoperability with existing architecture both upstream and downstream.